1977
DOI: 10.1042/bj1620453
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of amino-oxyacetate as an inhibitor

Abstract: Data are provided which indicate that pyruvate and/or acetaldehyde can reverse the inhibition of alanine aminotransferase and aspartate aminotransferase by amino-oxyacetate. It was shown that acetaldehyde could reverse the inhibition of gluconeogenesis from alanine and that pyruvate could reverse the inhibition of urea synthesis by amino-oxyacetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…Consistent with this, we found that the addition of aminooxyacetate, a general inhibitor of aminotransferases, essentially abolished urea synthesis (Fig. 1, 2nd row), also confirming results from other laboratories [22].…”
Section: Resultssupporting
confidence: 90%
“…Consistent with this, we found that the addition of aminooxyacetate, a general inhibitor of aminotransferases, essentially abolished urea synthesis (Fig. 1, 2nd row), also confirming results from other laboratories [22].…”
Section: Resultssupporting
confidence: 90%
“…Moreover, lactate release rates increased more than 10-fold in the presence of AOA. In contrast, AOA with pyruvate as a substrate significantly influenced neither the hemodynamic parameters nor the metabolite concentrations indicating that pyruvate can be metabolized after its uptake mitochondria (49 (65). These oscillations were sensitive to pharmacological manipulations of ryanodine-sensitive stores of intracellular Ca 2þ but not to TTX and L-type channel inhibitors (65).…”
Section: The Essential In Vivo Role Of the Masmentioning
confidence: 88%
“…In addition, we determined the influence of pyruvate on the oxidation of glutamate and glutamine since amino group acceptors can modulate glutamate metabolism [31] and may be therapeutically useful in pathological conditions characterized by ele vated concentrations of glutamate. In the present study we used the transaminase inhibitor aminooxyacetic acid (AOAA) [32] to obtain information about the impor tance of transamination enzymes in the metabolism of glutamate and glutamine by astrocytes.…”
Section: Introductionmentioning
confidence: 99%